Características de los sismos y sus efectos en las construcciones (Segunda de dos partes) - Jaime de la Colina Martínez; Horacio Ramírez de Alba (Ciencia Ergo Sum)
This work intends to divulge general concepts of earthquake engineering among no specialists starting from the basic concepts on seismology. It includes the origin and the characteristics of seismic movements and presents, in a basic level, the activity field of earthquake engineering. The way earthquakes affect structures, the seismic design process and the observed behavior of buildings during earthquakes are also presented.